Application of Molecularly Imprinted Microelectrode as a Promising Point-of-Care Biosensor for Alanine Aminotransferase Enzyme - Mostafa Ahmed Samy; Muhammed Abdel-Hamied Abdel-Tawab; Nour. T. Abdel-Ghani; Rasha M. El Nashar (Chemosensors, 2023)
Alanine amino transaminase (ALT) is an enzyme that can be used as a biomarker for liver injury and other diseases. In this work, we report the development of the first microelectrode based on a molecularly imprinted pyruvate oxidase enzyme to be applied as an electrochemical biosensor for ALT detection. The biosensor is based on pyruvate oxidase enzyme (POx), imprinted using 4-aminophenol (functional monomer-on-platinum microelectrode modified (PME)) with platinum nanoparticles and 4-aminoantypirine (4-AAP)/sodium pyruvate as an electrochemical indicator. The operational conditions of the biosensor were optimized and characterized morphologically using scanning electron microscopy (SEM) and electrochemically using electrochemical impedance spectroscopy (EIS). The biosensor was found to have a fast response towards ALT within a linear range of 25–700 U/L and a limit of detection of 2.97 U/L. The biosensor did not exhibit cross-reactivity towards other tested enzymes, including nicotinamide adenine dinucleotide (Beta-NAD), catalase (CAT), glutathione peroxidase (GPx), and L-glutathione reduced (GSH) enzymes. The biosensor was efficiently applied for the assay of ALT in plasma samples; with recovery values ranging from 99.80–103.82% and RSD of values 0.27–2.01% and these results were found to be comparable to those of the reference diagnostic kits, without any need for complicated procedures or protein extraction. In addition to being highly sensitive, low cost, and portable, the use of microelectrodes allows the application of the proposed sensor for point-of-care diagnostics of liver function and online monitoring of ALT levels in hospitalized patients without the need for withdrawing samples, which indicates the promising applicability of the presented ALT sensor for point-of-care diagnostics.